Dural based cavernoma of cerebral convexity – A rare case report - H. Mohamed Naleer; V. Vivek; Rav Tej Bathala; Venkata Shashank Davuluri; Jishnu; K. Ganesh; Lawrence D. Cruze (Interdisciplinary Neurosurgery, 2023)
Cerebral cavernous malformations occur in about 0.4–0.5 % of the population. They account for about 5–13 % of all vascular malformations of the central nervous system, commonly occurring in the cerebral parenchyma. Very few cases of cavernomas arising from the convexity dura mater have been reported in literature. Cavernous malformations arising from the dura were earlier termed “dural-based cavernous angioma“, ”dural-based cavernous malformation“, ”dural cavernous angioma“ or ”extra-axial cavernous angioma”. Currently they have been classified as “other” venous malformation as per the recent ISSVA classification. Our patient, a 41 year old lady presented with complaints of low back pain radiating to the left lower limb of 20 days duration. During evaluation of associated headache she was found to have a left parietal dural based lesion suggestive of meningioma. Patient underwent craniotomy and excision of lesion. Intraop and histopathological findings were suggestive of dura based cavernous angioma of the cerebral convexity. This case is being reported for its rarity.